EFFECTIVE VILLAGE OWNED ENTERPRISES (BUMDes) HR DEVELOPMENT IN TENILO VILLAGE - Yulfin Dama; Azis Rachman; Samin Latif (Journal of Economic, Business, and Administration (JEBA), 2021)
This research aims 1) to find out the empirical model of human resource development of BUMDes Management in Tenilo Village. and 2) to find out the obstacles in the development of BUMDes Management HUMAN RESOURCES in Tenilo Village at this time.The method in this research is to use a qualitative approach by investigating cases and phenomena from informant sources that explain why and how the problems that occur in BUMDesKarya Bersama. Using data analysis consisting of 3, namely data collection, data reduction, presentation of data, and withdrawal of conclusions or verification. The results showed that 1) The application of empirical model benchmarking in BUMDes human resources joint work in Tenilo Village in developing BUMDes was considered not to be effective. It is indicated that so far, the manager or HR owned does not have mature abilities, often the change or even the implementation of BUMDes development training for HR is only limited to 1-day training even most material provision, where the rest is only done in the form of business development assistance. 2) The biggest obstacles experienced in the development of BUMDesKarya Bersama human resources in Tenilo Village are why there are BUMDes institutions that are limited in funds and constrained by existing policy regulations, the willingness of HUMAN RESOURCES to survive in managing BUMDes, and due to the ability of HUMAN RESOURCES that are only widely equipped with material provision.